EXTERNAL AND INTERNAL BANKING FACTORS ON THE INTERMEDIATION FUNCTION OF STATE-OWNED BANKS - Jahidah, Nurul; Sofyan, Mohammad; Suteja, Jaja (Jurnal Riset Bisnis dan Manajemen, 2024)
This research aims to analyze external and internal factors on the intermediation function of state-owned banks. The method used is Autoregressive Distributed Lag with time series data for 2008 - 2022 for two research models, namely Third-Party Fund Growth and Credit Growth. The research results show that external and internal factors influence the growth of third-party funds, namely that in the long-term inflation has a significant negative effect, BI rate and Economic Growth have a significant positive effect. In the short term, inflation and economic growth have an insignificant positive effect, BI-rate has an insignificant negative effect. In the model of external and internal factors that influence credit growth, it is known that in the long term, the growth of third-party funds, BI-Rate, and Economic Growth have a significant positive effect, CAR, NPL, and Inflation have a significant negative effect. In the short term, the growth of third-party funds, CAR, NPL, BI-rate, and Economic Growth have an insignificant negative effect, while inflation has a significant positive effect.